MEDIA GAMBAR DAPAT MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA PADA TEMA PEMBELAJARAN KELUARGA KELAS I SD NEGERI 004 ROKAN IV KOTO TAHUN PELAJARAN 2015/2016 - Suslawati Suslawati (STKIP Rokania Pasir Pangaraian, 2019)
Improvement of learning has been carried out with the title of using media images can improve Student Mathematics Learning Outcomes in Family Thematic Themes Learning Class I 004 Rokan IV Koto Public Elementary School 2014/2015 Academic Year held in March to June 2015. Subjects of this study were class I students as much as 20 people consisted of 12 men and 8 women. The measured parameters are student learning outcomes including absorption and mastery of learning obtained from the post test and Daily Deuteronomy, student learning activities and teacher activities. Results Before Improvement with an average of 64.75 with sufficient categories, in the first cycle the average was 77.5 with the Good category and the second cycle averaged 85.25 in the good category. Student learning completeness before improvement 10 (50.0%), in the first cycle there were 15 students completed (75.0%) while classical completeness was achieved in the second cycle of 19 (95.0%). Student activity, activities working on worksheets with their groups, pasting pieces of pictures and giving information on the image, asking questions and answering questions. The activity percentage of the first cycle averaged 70.16 with the Good category, in the second cycle it increased to 86.66 with a very good category. The teacher's activity experienced an increase in the first cycle on average 85 with excellent categories, the second cycle averaged 95 with very good categories. From the results of the study it can be concluded that the Utilization of Image Media Can Improve Student Mathematics Learning Outcomes in Thematic Learning Family Themes